2011
DOI: 10.1152/physiolgenomics.00155.2010
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the luteal transcriptome: potential mechanisms mediating stage-specific luteolytic response of the corpus luteum to prostaglandin F

Abstract: The objective of this study was to identify prostaglandin F(2α) (PG)-induced changes in the transcriptome of bovine corpora lutea (CL) that are specific to mature, PG-responsive (day 11) CL vs. developing (day 4) CL, which do not undergo luteolysis in response to PG administration. CL were collected at 0, 4, and 24 h after PG injection on days 4 and 11 of the estrous cycle (n = 5 per day and time point), and microarray analysis was performed with GeneChip Bovine Genome Arrays. Data normalization was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 49 publications
16
63
1
Order By: Relevance
“…Specifically, during luteolysis, immune cell infiltration to the CL increases (Penny, 2000) and they are considered to play a role in luteolysis. Although these immune cells are not responsive to PGF 2α in dCL, luteal cells respond to PGF 2α by increasing the expression of those genes that have regulatory functions on immune cells in mCL (Mondal et al, 2011). Therefore, the stimulation of TLR expression in luteal cells in mCL and rCL as observed in the present study may relate to an increased active immune status of the CL.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Specifically, during luteolysis, immune cell infiltration to the CL increases (Penny, 2000) and they are considered to play a role in luteolysis. Although these immune cells are not responsive to PGF 2α in dCL, luteal cells respond to PGF 2α by increasing the expression of those genes that have regulatory functions on immune cells in mCL (Mondal et al, 2011). Therefore, the stimulation of TLR expression in luteal cells in mCL and rCL as observed in the present study may relate to an increased active immune status of the CL.…”
Section: Discussionmentioning
confidence: 48%
“…Since PKCε is a critical component of TLR4 signaling (McGettrick et al, 2006) and expression of both PKCε and TLR4 increased at the same stages of the CL, TLR4 is possibly a critical component for the PGF 2α response in the CL, implying a potential role of TLR4 in the acquisition of luteolytic capacity. Similarly, immune related genes increased only after PGF 2α induction in mCL compared to dCL (Mondal et al, 2011). Moreover, enhanced populations of specific types of immune cells and cell-to-cell communication between immune and the other types of CL cells in the mature stage clearly indicate immune regulation of the luteolytic pathway (Poole and Pate 2012;Penny 2000).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Recent study showed that PGF 2␣ administration suppressed the expression of luteotropic factors and stimulated the expression of luteolytic factors that contributed to functional luteolysis (Berisha et al, 2010). Furthermore, there were multiple studies suggesting that PGF 2␣ could induce mRNA for many pathways and set the stage-specific gene expression that resulted in luteolysis (Atli et al, 2012;Bishop et al, 2012;Mondal et al, 2011). PGF binds and activates a Gqcoupled receptor on its target cells to activate phospholipase C, which results in increased free intracellular calcium (Currie et al, 1992;Davis et al, 1987;Rodway et al, 1992) and PKC activity (Davis et al, 1989).…”
Section: Introductionmentioning
confidence: 99%